2020
DOI: 10.1182/bloodadvances.2020003083
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of venous thromboembolism in 6513 patients with COVID-19: a retrospective study

Abstract: Patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) appear to be at increased risk for venous thromboembolism (VTE), especially if they become critically ill with COVID-19. Some centers have reported very high rates of thrombosis despite anticoagulant prophylaxis. The electronic health record (EHR) of a New Orleans–based health system was searched for all patients with polymerase chain reaction–confirmed SARS-CoV-2 infection who were either admitted to hospital or treated and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
68
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 13 publications
11
68
1
3
Order By: Relevance
“…For VTE, all events except for one occurred in the ICU. The rate of VTE in the current study was much lower than that in previously published studies [ 10 14 ] but consistent with that in other studies [ 15 – 18 ]. In a multicenter study in the Netherlands ( n = 184) [ 11 ] in which all patients were admitted to the ICU and received standardized doses of nadroparin and a dose escalation to 5700 IU BID at some point during admission in selected patients, the cumulative composite outcome of venous and arterial events was 49 % when adjusting for a competing risk of death.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For VTE, all events except for one occurred in the ICU. The rate of VTE in the current study was much lower than that in previously published studies [ 10 14 ] but consistent with that in other studies [ 15 – 18 ]. In a multicenter study in the Netherlands ( n = 184) [ 11 ] in which all patients were admitted to the ICU and received standardized doses of nadroparin and a dose escalation to 5700 IU BID at some point during admission in selected patients, the cumulative composite outcome of venous and arterial events was 49 % when adjusting for a competing risk of death.…”
Section: Discussionsupporting
confidence: 92%
“…Propensity score matching was used, and it was determined that the COVID-19 ARDS patients had higher rates of thrombotic events than those with non-COVID-19 ARDS (11.7 % versus 2.1 %). In one of the largest studies that included 6513 patients (637 patients required mechanical ventilation), the rate of VTE within the hospitalized cohort was 3.1 %, and that in the subgroup of patients who required mechanical ventilation at any time during hospitalization was 7.2 % [ 15 ]. In another multicenter retrospective study with 400 admitted COVID-19 patients, the VTE (confirmed or presumed) rates were 6 %, 3.91 % and 10.4 % in all patients, noncritically ill patients and critically ill patients, respectively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the incidence of postdischarge VaTE following admission for COVID‐19 is low but not negligible. Our findings are in line with published literature reporting a cumulative VaTE incidence of 2.5%, with VTE rates ranging from 0.14% to 0.6% following COVID‐19 hospital discharge 2‐4 . Although we did not compare COVID to non‐COVID discharges, other studies have also reported low 30‐day postdischarge VTE incidence rates that do not significantly differ between medical patients with and without COVID‐19 2 .…”
Section: Discussionsupporting
confidence: 91%
“…While we attempted to adjust for significant confounders in our logistic regression model (age and ICU admission), it is possible that there were other unmeasured risk factors that contributed to differences in use of postdischarge anticoagulation. In addition, we considered whether higher inpatient anticoagulation dosing may have contributed to the low incidence of outpatient events, but we found a comparable rate of outpatient VaTEs as studies that used standard dose prophylaxis in inpatients 2‐4 . Finally, the low number of VaTEs in our patient cohort, as well as the confounding influence of postdischarge anticoagulation, limited our ability to investigate the impact of other risk factors on the outcome.…”
Section: Discussionmentioning
confidence: 96%